Penguatan Identitas Kebahasaan Indonesia dalam Kurikulum: Perspektif Siswa Tentang Bahasa Nasional di Era Global - Santhi Pertiwi; Rugaiyah; Masduki Ahmad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to explore students' perceptions of Bahasa Indonesia as a national identity in the era of globalization and their potential role in promoting the language internationally. Using a qualitative approach with a phenomenological method, this study involved 20 junior high school students in East Jakarta who were selected purposively. Data were collected through semi-structured interviews and limited observations, then analyzed using open, axial, and selective coding techniques. The results showed that students viewed Bahasa Indonesia as a symbol of national unity, felt proud of the international recognition of the language, and acknowledged the ease of the structure of Bahasa Indonesia compared to foreign languages. In addition, students were aware of their strategic role in promoting the language through social media and digital content, and saw the potential of Bahasa Indonesia as an international language that could strengthen the nation's competitiveness and cultural identity. These findings indicate the importance of updating the Bahasa Indonesia curriculum that does not only focus on technical aspects, but also builds national and global awareness.